Francesco Salviati and the Horses of San Marco - Gregory, Sharon (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2024)
In 1539, Florence’s newly elected Duke Cosimo I de’ Medici began to turn the Palazzo della Signoria into his ducal residence. The first major artistic work he commissioned for the palazzo was a cycle of frescoes by Francesco Salviati (1543–48), with scenes from the life of Marcus Furius Camillus. Salviati’s Triumph of Furius Camillus fresco is discussed in light of a preparatory drawing, which shows a chariot drawn by an animated group of horses very like the famous horses of San Marco in Venice (where Salviati had worked from 1539 until 1541), and very unlike the regimented group that draws the chariot in the final fresco. In the wake of Savonarolan reforms to the Florentine government after the expulsion of the Medici, the Venetian quadriga cannot have been politically acceptable to Duke Cosimo. Salviati presumably altered his design to better accord with Cosimo’s self-association with imperial Rome.